The Philippine islands. A political, geographical, ethnographical, social and commercial history of the Philippine archipelago and its political dependencies, embracing the whole period of Spanish rule - Foreman, John (Kelly and Walsh, Ltd., 1899)
"Long years of personal acquaintance with some of the active movers in the Revolutionary Party enabled me to estimate their aspirations. My associations with Spain and Spaniards since my boyhood helped me, as an eye-witness of the outbreak of the rebellion, to judge of the counterpart to that movement. My connection with the American Peace Commission in Paris afforded me an opportunity of appreciating the noble efforts of a free people to raise the weight of monastic oppression from millions of their fellow creatures."